The Relationship Between Nurse Caring and The Level of Anxiety of Patients' Families in the ICU Room RSUD RAA Soewondo Pati - Emma Setiyo Wulan; Lini Muntiari; Hirza Ainin Nur (International Journal Of Health Science, 2025)
Caring nurses are nurses' attitude of caring for patients, treating patients with sincerity, affection, sincerity, providing support both through communication and direct action. Anxiety is a psychological condition where a person experiences excessive anxiety constantly and is difficult to control so that it can have a bad impact on daily life. Anxiety must be lowered so as not to adversely affect physical and psychological disorders, fatigue and family helplessness in dealing with these stressful situations. The purpose of this study is to determine the relationship between nurse care and the level of anxiety of patients' families in the Intensive Care Unit (ICU) room of RAA Soewondo Pati Hospital. This study uses a type of correlational quantitative research with a cross sectional approach. The population in this study was 122 patients, with the calculation of the Arikunto formula, a sample of 31 respondents was obtained. The research instrument used was the caring CPS (Caring Professional Scale) questionnaire, while to measure the level of anxiety, the ZS-RAS (Zung Self-Rating Anxiety Scale) questionnaire was used. The majority of respondents showed good caring behavior of nurses as many as 22 respondents (71%) with mild anxiety levels of 15 respondents (48.4%), moderate anxiety as many as 6 respondents (19.4%), and severe anxiety as many as 1 respondent (3.2%). The caring behavior of nurses was sufficient as many as 9 respondents (29%) with a level of mild anxiety of 1 respondent (3.2%), moderate anxiety as many as 6 respondents (19.4%), and severe anxiety as many as 2 respondents (6.5%). The results of the spearmen rank (Rho) statistical test obtained a significant value (p value) of 0.002. There was a relationship between the caring behavior of nurses and the level of anxiety of patients' families in the Intensive Care Unit (ICU) room of RAA Soewondo Pati Hospital